POTENTIAL ABILITY OF THE SOLANUM-FEEDING LADYBIRD BEETLE HENOSEPILACHNA DIFFINIS (COLEOPTERA; COCCINELLIDAE) TO USE THE INTRODUCED FABACEOUS PLANT CENTROSEMA MOLLE - Kikuta, Shogo; Fujiyama, Naoyuki; Kahono, Sih; Kobayashi, Norio; Hartini, Sri; Katakura, Haruo (Research Center for Biology, 2013)
Host specificity has been a major factor in generating the tremendous diversity of phytophagous arthropods. Studies of adaptation to introduced or invasive plant species provide an opportunity to investigate incipient evolutionary changes in host specificity. We investigated the cryptic ability of the Asian tropical herbivorous ladybird beetle Henosepilachna diffinis to feed on the fabaceous weed